(untitled) (Swiss Medical Weekly, 2014)
Rheumatoid arthritis (RA) is a chronic, systemic, inflammatory disease, which results in joint destruction and permanent disability. The advent of disease-modifying antirheumatic drugs (DMARDs) has made a profound impact on the outcome and prognosis of RA. Methotrexate (MTX) is a central agent in RA therapy, and is used either alone or in combination with biological DMARDs. However, a large proportion of RA patients (20%–40%) either do not respond to or are unable to tolerate MTX or the alternative agents used in place of MTX (including leflunomide, sulfasalazine, azathioprine, hydroxycholoquine and combination DMARDs). For these patients, monotherapy with biological DMARDs is a key treatment option that balances tolerability with improved clinical outcomes. This article reviews the data for four biological agents approved for use as monotherapy in Switzerland (adalimumab, certolizumab pegol, etanercept and tocilizumab) in order to formulate a consensus statement on their roles in biologic monotherapy of RA.